Endoscopic Colonic Decompression - Norman E Marcon (Canadian Journal of Gastroenterology)
Colonic pseudo-obscruction, or Ogilvie's syndrome, is characterized by marked distension of the large intestine in the absence of mechanical obstruction. Etiology is unknown. Left untreated, it may lead to perforation with a mortality of 46%. Reversible causes such as electrolyte imbalance, anricholinergic drugs, analgesics, steroids or hypothyro1d1sm should he excluded. Early recognition of pseudo-obstruction with institution of supportive means followed by colonoscopic decompression with rube placement should be successful in all cases.